Leadership in Contemporary Leadership Studies and Management Discourse - Parashchenko, Liudmyla; Паращенко, Людмила Іванівна; Паращенко, Людмила (Scientific Center of Innovative Research, 2025)
Leadership research has evolved into an interdisciplinary domain integrating management, organizational behavior, psychology, sociology, public administration, and educational studies. This evolution shifts attention from individual traits and formal authority toward leadership as a context-dependent process of influence embedded in relationships, routines, and institutional constraints, which is especially salient for schools and universities where expertise is distributed and accountability is multi-layered across actors and governance levels. The chapter explains why leadership retains persistent definitional plurality and proposes an integrative lens for analysing leadership in educational organizations without collapsing it into a single paradigm. A structured conceptual synthesis is conducted across major leadership traditions and education-oriented research, complemented by mechanism mapping that aligns approaches by unit of analysis, assumed sources of influence (authority, expertise, values, networks), and expected organizational effects. The synthesis identifies a stable minimal core of leadership as purposeful influence oriented toward shared goals and enacted through relational and collective dynamics. Definitional diversity follows systematic theoretical choices about level (individual, dyad, group, system) and mechanism, including legitimation, sensemaking, distribution of practice, instructional focus, and adaptive coordination under complexity. For education, pathways to outcomes tend to operate via instructional quality, teacher collaboration, professional learning, and trust-based coordination. It differentiates leadership from management and clarifies implications for capacity building and accountability. Plurality of definitions is analytically informative because it reveals distinct levers for improvement and different risks of reductionism. Educational governance benefits from conceptualizing leadership as a configurable set of socio organizational relations that complements, but is not identical to, managerial administration and formal control. Future studies should test leadership configurations using multi-level mixed methods, connect relational and distributed measures to student learning and staff well-being, and examine how digitalization, inequality, and crisis conditions reshape legitimacy, responsibility, and the boundaries of leadership practice
Keywords: educational leadership; definitional plurality; interdisciplinary leadership studies; mechanism mapping; legitimacy; accountability; instructional leadership; distributed leadership; relational leadership; complexity leadership; eleadership; governance design